(untitled) (American Journal of Islam and Society, 1987)
Introduction The idea of Islamizing the sciences, whether they be natural or social, raises some philosophical and methodological questions which must, in my view, be settled before any serious program of Islamization can be carried out. I shall, in this paper, do no more than give examples of these fundamental questions, give brief answers to some of them and throw out hints as to how others can be answered. In doing so I shall do my best to keep as close as possible to the Qur’an and the Sunnah, but I cannot claim that whatever answers I give are the Islamic answers to the questions I raise. Philosophical Questions What does it mean to Islamize knowledge? The elucidation of this question and the answer to it are given in the following imaginary dialogue between a Western philosopher, call him W, and a Muslim propounder of the Islamization of knowledge, call him M. W: Is Islam compatible with all forms of truth? M: Certainly. W Would you agree that if something is known, then it is true, i.e. that knowledge implies truth? M: I agree provided that you make a distinction between knowledge and claims to knowledge and provided that you agree that there are degrees of truth. W I accept the qualifications, but if knowledge implies truth, and truth in all its forms is compatible with Islam, then knowledge in all its forms is Islamic. But if this is so, what does it mean then to Islamize knowledge? How do you make something Islamic which is already so? Or is it your intention merely to give each form of knowledge an Islamic flavour by injecting an ayat here, imposing a hadith there, making an opening with bismillahi-rrahmani-rrahim and a closing with alhamdu lillahi rabbi-l’alamin? ...